Elite Universities and the Intergenerational Transmission of Human and Social Capital - Barrios-Fernández, Andrés; Neilson, Christopher; Zimmerman, Seth (American Economic Review, 2026)
Do elite colleges help talented students join the social elite or help incumbent elites retain their positions? We combine intergenerationally linked data from Chile with a regression discontinuity design to show that, looking across generations, elite colleges do both. Lower-status individuals who gain admission to elite college programs transform their children’s social environment. Children become more likely to attend high-status private schools and colleges and to live near and befriend high-status peers. In contrast, academic achievement is unaffected. Simulations combining descriptive and quasi-experimental findings show that elite colleges tighten the link between social and human capital while decreasing intergenerational social mobility. (JEL I23, I26, J24, J62, O15, Z13)